2013
DOI: 10.2478/euco-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, Farm Diversification and Plurality of Rurality: Case Study of Croatia

Abstract: Plurality is considered to be one of the most important indicators of rurality in the contemporary society. But in what sense can plurality and diversified geographic context of countryside make a difference for development of farm tourism, if any? This paper aims to explore the significance of rural diversity of Croatia for farm diversification into leisure-orientated activities. The main method is comparison of spatial distribution of those farms, on the one hand, and seven different types of rural areas, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Despite the undeniable importance of the nature of a locality and of the agritourist space, in which any farm operates and which is, at the same time, co-determined by this farm, this crucial geographical/spatial determinant of the development of agritourism has been explored only to a very limited extent in the relevant literature, and studies focused on these issues remain sporadic (see, for instance, Klapka et al, 2005;Cigale et al, 2013;Lukić, 2013). Marketing and management, motivation for the involvement of farmers in this type of business, and their attitudes monitored at a national level, have received much more attention and consideration at this time (Nilsson, 2002;Sharpley, Vass, 2006;Haugen, Vik, 2008;Dömeova, Jindrova, 2011;Forbord et al, 2012).…”
Section: Key Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the undeniable importance of the nature of a locality and of the agritourist space, in which any farm operates and which is, at the same time, co-determined by this farm, this crucial geographical/spatial determinant of the development of agritourism has been explored only to a very limited extent in the relevant literature, and studies focused on these issues remain sporadic (see, for instance, Klapka et al, 2005;Cigale et al, 2013;Lukić, 2013). Marketing and management, motivation for the involvement of farmers in this type of business, and their attitudes monitored at a national level, have received much more attention and consideration at this time (Nilsson, 2002;Sharpley, Vass, 2006;Haugen, Vik, 2008;Dömeova, Jindrova, 2011;Forbord et al, 2012).…”
Section: Key Theoretical Backgroundmentioning
confidence: 99%
“…Many studies reveal that agritourism is indeed concentrated in areas which are already established as popular tourist destinations, as "in this case, visitors are willing to pay a higher price for a firm located in a region that is rich in tourist attractions" (Fleischer, Tchetchik, 2005), and consequently, in popular tourist areas agritourism can generate greater farm revenues (Sharpley, Vass, 2006). For example, Lukić (2013) reported that most of the households with agricultural production -tourism, accommodation and other leisure activities -are located in the littoral counties of Croatia, reflecting the importance of mass-tourism for the development of farm tourism.…”
Section: Key Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…however, is it possible to solve all of the problems in every rural area by developing tourism there? tourism and recreation have been for decades one of the responses to various challenges and threats to rural areas, often even a solution for all structural problems of the rural areas (adamowicz 2010;baležentis et al 2012;baum 2011;butler et al 1998;cawley and gillmor 2008;hall et al 2003;ilbery 1998;látková and Vogt 2011;lukić 2013;Sharpley 2002;Wilson et al 2001;Woods 2005). literature which examines the role of tourism in rural areas in poland and croatia is still limited in scope in comparison with the western european countries.…”
mentioning
confidence: 99%